The protective role of Visudyne eyeglass® against VEGF synthesis after photodynamic therapy with verteporfin - Turkcuoglu, Peykan; Ilhan, Nevin; Kurt, Julide; Aydemir, Orhan; Celiker, Uelkue (Wiley-Blackwell Publishing, Inc, 2009)
Purpose: We aimed to determine the extent of protection provided by Visudyne eyeglass (R) against vascular endothelial growth factor (VEGF) synthesis following photodynamic therapy (PDT). Methods: Three groups with 14 rabbits in each were established. These consisted of a control (dextrose infusion) group, an infusion (verteporfin infusion) group and an irradiation (verteporfin infusion + irradiation) group. One eye in each animal was closed with Visudyne eyeglass (R) and the other by eyelid sutures. The rabbits were exposed to daylight for 30 mins at 2 and 48 hours after the infusion was administered. Half the animals in each group were killed on day 5. The remaining animals were killed on day 10. Levels of VEGF in homogenized retina and choroids were analysed with an ELISA (enzyme-linked immunosorbent assay). Results: Mean VEGF levels, in pg/mg protein, on days 5 and 10 in the control + glass, control + suture, infusion + glass, infusion + suture, irradiation + glass and irradiation + suture subgroups were, respectively: 1.69 +/- 0.67, 1.91 +/- 0.44; 1.75 +/- 0.69, 1.93 +/- 0.53; 2.30 +/- 0.77, 3.47 +/- 2.02; 1.90 +/- 1.00, 2.93 +/- 0.16; 4.39 +/- 2.74, 13.63 +/- 5.25; 3.38 +/- 1.05, 7.37 +/- 2.12. On day 10, VEGF levels were significantly higher in the infusion and irradiation groups compared with the control group (p < 0.05). There were no statistically significant differences between glass and suture samples on days 5 and 10 in the infusion group, or on day 5 in the irradiation group. However, on day 10, the mean VEGF level in eyes closed with Visudyne eyeglass (R) in the irradiation group was significantly higher than in sutured eyes (p = 0.011). Conclusions: Visudyne eyeglass (R) offers full protection against VEGF increases caused by verteporfin infusion but is only partially protective in eyes exposed to sensitizing light.
Keywords: photodynamic therapy; protection; VEGF; Visudyne eyeglass (R)